Analysis of oligo(deoxynucleoside phosphorothioate)s and their diastereomeric composition. - Wilk, A (1995)
Short oligo(deoxynucleoside phosphorothioate)s were analyzed as a pool of individual diastereomeric species. The composition of such mixtures, determined by means of HPLC, indicates that consecutive couplings in commonly used phosphoramidite chemistry lead to increasing contents of the Rp isomer. Methods of analysis and mathematical basis for diastereomeric composition are discussed. Data presented include all 16 possible combinations of nucleosides in dinucleotide phosphorothioates, as well as examples of trimers and tetramers.